Economic Development as a matter of political geography - Streb, Jorge (Estudios de Economía, 2016)
Can limited government be a driving force of economic development? This idea goes back to Montesquieu, and is closely related to recent research in institutional economics. Measuring limited government with the Henisz political constraints index, and economic development with income per capita, the paper first does a causality test to see whether political constraints lead income per capita. Since both are persistent variables, their differences are analyzed. The evidence from the 1960-1990 period indeed suggests that increases in political constraints precede economic growth. The effect of political constraints might take a long time period to set in, so a second test looks at the link between income per capita and polity persistence, conditioned on the degree of political constraints. Polity persistence is positively linked to income per capita with high political constraints, but there is no link with low political constraints. This broader evidence suggests that limited government has been conducive to economic development over the long run.